2014
DOI: 10.1097/ta.0b013e3182ab1b4d
|View full text |Cite
|
Sign up to set email alerts
|

Blunt cerebrovascular injury screening guidelines

Abstract: Diagnostic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 11 publications
2
49
0
Order By: Relevance
“…Specifically, the cost of stroke was calculated by dividing the lifetime stroke cost obtained by the difference between the average age at occurrence of BCVI (40 years of age) and the average life span of people in the United States (78.9 years of age). 6,7,[19][20][21] We acknowledge that our methodology for calculating the cost might be inaccurate, but the value is close to that reported in recent literature. 22 A list of all parameters and their values is presented on the On-line Table. There are several assumptions made in this model:…”
Section: Costs and Outcomesmentioning
confidence: 48%
See 3 more Smart Citations
“…Specifically, the cost of stroke was calculated by dividing the lifetime stroke cost obtained by the difference between the average age at occurrence of BCVI (40 years of age) and the average life span of people in the United States (78.9 years of age). 6,7,[19][20][21] We acknowledge that our methodology for calculating the cost might be inaccurate, but the value is close to that reported in recent literature. 22 A list of all parameters and their values is presented on the On-line Table. There are several assumptions made in this model:…”
Section: Costs and Outcomesmentioning
confidence: 48%
“…Four studies reported the number of BCVIs with high-risk factors, and the weighted average was obtained to extrapolate the incidence of BCVI in high-risk patients. 1,[6][7][8]18 The proportion of high-risk populations in all blunt trauma admissions was derived from the weighted average of 2 studies totaling nearly 30,000 patients. 6,7…”
Section: Clinical Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 Initially, digital subtraction angiography was used for diagnosis, but with advances in technology, CTA is considered the imaging technique of choice, with a sensitivity and specificity of nearly 98% and 100%, respectively. 11,12 Various screening criteria have been proposed for patients with blunt trauma, with the Modified Denver Criteria being the most accepted [13][14][15] ; however, other criteria (such as the Memphis Criteria 16 and Boston Criteria 17 ) may make implementation of protocol confusing and challenging for practitioners. Also, there are no specific guidelines for screening these injuries in the pediatric population.…”
mentioning
confidence: 99%